1997
DOI: 10.1038/sj.bmt.1700971
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for therapy-related myelodysplasia: comparison with primary myelodysplasia

Abstract: Summary:use of intensive chemotherapy, the incidence of therapyrelated MDS is rising. [4][5][6][7] There are also recent reports of therapy-related MDS occurring after autologous transplants Therapy-related myelodysplasia (MDS) is a fatal marrow disorder distinct from primary MDS. We examined for lymphoma and breast cancer. 8-10The prognosis for patients with therapy-related MDS is the efficacy of bone marrow transplantation (BMT) as a treatment for patients with therapy-related MDS.poor. The median survival i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 5 publications
2
51
1
1
Order By: Relevance
“…The outcome after bone marrow transplant for therapy-related AML is also poor. A study from Seattle reported a 5-year DFS of 7.8% for 17 adults patients with therapy-related AML 17 while Ballen et al 18 reported 24% DFS at 3 years. For pediatric patients with epipodophyllotoxin-induced AML, Sandler et al 7 reported eight patients receiving allogeneic transplants and two patients receiving autografts after previous therapy for ALL.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome after bone marrow transplant for therapy-related AML is also poor. A study from Seattle reported a 5-year DFS of 7.8% for 17 adults patients with therapy-related AML 17 while Ballen et al 18 reported 24% DFS at 3 years. For pediatric patients with epipodophyllotoxin-induced AML, Sandler et al 7 reported eight patients receiving allogeneic transplants and two patients receiving autografts after previous therapy for ALL.…”
Section: Discussionmentioning
confidence: 99%
“…18 Even for therapy-related myelodysplasia, transplantation seems to be favorable for long-term disease-free survival. 19 …”
Section: Outcomementioning
confidence: 99%
“…13 In a small single-center study including 18 patients with MDS, the disease-free survival after allogeneic stem cell transplantation was only 24% for t-MDS in comparison to 43% for primary MDS. 16 However, one might keep in mind that the patient population in our study is highly selected including mostly patients with AML at diagnosis, who were chemosensitive and in CR at the time of transplantation. Similar to the reported risk factor for allogeneic stem cell transplantation in t-MDS/t-AML, 13 lower age and CR are most important risk factors for OS after autologous stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a review of 644 patients with t-AML treated with standard-AML-induction protocols, only 28% achieved a CR. 11 Importantly, a small number of patients with t-AML who have favorable cytogenetic abnormalities, such as t(8;21), t(15;17), or inv (16), have a considerably better outcome, not markedly different from the high response rate observed with the same abnormalities in de novo AML. 12 Allogeneic stem cell transplantation is proposed to be the only curative treatment approach in t-MDS/AML.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation